MicroRNAs in Cardiometabolic Diseases - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2013)
BACKGROUND: MicroRNAs (miRNAs) are ~22-nucleotide noncoding RNAs with critical functions in multiple physiological and pathological processes. An explosion of reports on the discovery and characterization of different miRNA species and their involvement in almost every aspect of cardiac biology and diseases has established an exciting new dimension in gene regulation networks for cardiac development and pathogenesis.CONTENT: Alterations in the metabolic control of lipid and glucose homeostasis predispose an individual to develop cardiometabolic diseases, such as type 2 diabetes mellitus and atherosclerosis. Work over the last years has suggested that miRNAs play an important role in regulating these physiological processes. Besides a cell-specific transcription factor profile, cell-specific miRNA-regulated gene expression is integral to cell fate and activation decisions. Thus, the cell types involved in atherosclerosis, vascular disease, and its myocardial sequelae may be differentially regulated by distinct miRNAs, thereby controlling highly complex processes, for example, smooth muscle cell phenotype and inflammatory responses of endothelial cells or macrophages. The recent advancements in using miRNAs as circulating biomarkers or therapeutic modalities, will hopefully be able to provide a strong basis for future research to further expand our insights into miRNA function in cardiovascular biology.SUMMARY: MiRNAs are small, noncoding RNAs that function as post-transcriptional regulators of gene expression. They are potent modulators of diverse biological processes and pathologies. Recent findings demonstrated the importance of miRNAs in the vasculature and the orchestration of lipid metabolism and glucose homeostasis. MiRNA networks represent an additional layer of regulation for gene expression that absorbs perturbations and ensures the robustness of biological systems. A detailed understanding of the molecular and cellular mechanisms of miRNA-mediated effects on metabolism and vascular pathophysiology could pave the way for the development of novel diagnostic markers and therapeutic approaches.KEYWORDS: microRNA, lipid metabolism, glucose homeostasis, vascular endothelium, vascular smooth muscle, atherosclerosis